PENGARUH BUDAYA ORGANISASI, KOMITMEN DAN MOTIVASI KERJA TERHADAP KINERJA PERSONEL SATUAN LALU LINTAS POLRES PAMEKASAN - jurnalmap map; Mohamad Khomaedy; Wasis Budiarto; Indra Prasetyo (MAP (Jurnal Manajemen dan Administrasi Publik), 2019)
ABSTRACT This research was conducted in the Pamekasan Police Traffic Unit with a total sample of 85 personnel. Data analysis using SPSS, this type of research is explanatory research using quantitative research approaches. The results of the study show that: 1). Simultaneously, organizational culture, commitment, work motivation have a significant influence on the performance of Pamekasan Police Traffic Unit personnel. 2). Partially, organizational culture, commitment, work motivation have a significant influence on the performance of Pamekasan Police Traffic Unit personnel. Based on the results of the t test it is known that organizational culture has a dominant influence on the performance of personnel on the performance of the Pamekasan Police Traffic Unit personnel; evidenced then it is known that commitment has a positive and significant effect on the performance of the Pamekasan Police Traffic Unit personnel. Keywords: Organizational Culture (X1), Commitment (X2), Work Motivation (X3), And The Performance of Personnel (Y)